Exporting Art from Ireland: The Alfred Beit Foundation and the Protection of Cultural Property - Oakes, Ted (Irish Journal of Arts Management and Cultural Policy, 2017)
This article examines the legislative framework in place in Ireland, before and after the events of the Beit sale in 2015. In April 2015, Christies of London announced the sale of several old Masters paintings owned by the Alfred Beit Foundation. There was an immediate hostile public reaction. This attempted sale highlighted weaknesses in the existing Irish art export regime. The sale was challenged in court by An Taisce – the National Trust for Ireland - and the court case began a judicial review of the licensing regime. This initiated a series of changes by the Irish government, e.g. extension of the criteria for the issuing of export licences to the European Union. This is a minor change that does not resolve the greater concerns relating to property rights vs. heritage protection. In addition, it exposed the absence of political will to prioritise and legislate for cultural heritage protection in Ireland, in particular, for non-archaeological artefacts. The purpose of this article is to acknowledge that changes were made to the system, and to highlight continuing weaknesses in the regime.